Enhancing Ninth-Grade Students’ Vocabulary Through Word Mapping Game at MTs Muhammadiyah Al-Haq Palu - Dinarti; Manurung, Konder; Lebagi, Desrin; Thamrin, Nur Sehang (LPPM Universitas Advent Indonesia, 2025)
This study aims to determine whether the Word Mapping Game is effective in increasing vocabulary mastery of the ninth-grade students at MTs Muhammadiyah Al-Haq Palu. Students of grade IX participated in this research. Two classes were identified as control and experimental classes in this quasi-experimental research design. The researcher used pretest and posttest to collect data. Then, SPSS version 24 was used to analyze the collected data. The results showed that the mean posttest score of students in the experimental class 77.08 was higher than the mean score in the control class 61.85. Furthermore, based on the results of Mann-Whitney U, the sig (2 tailed) value 0.008 was lower than 0.05. It indicated that the alternative hypothesis was accepted and the null hypothesis was rejected. Therefore, the use of Word Mapping Game can increase the vocabulary mastery of the ninth-grade students at MTs Muhammadiyah Al-Haq Palu.